(untitled) (Conferencea, 2023)
Reliable and secure operation of data networks, computer systems and mobile devices is the most important condition for the functioning of the state and for maintaining economic stability. The safe operation of key information systems in common use is influenced by many factors: cyberattacks, disorders caused by physical impact, failure of hardware and software, humane mistakes. These events demonstrate how modern society depends on stability of information systems.